The impact of the court of justice of the European union on the turkish legal system - Karan, U. (Oxford University Press, 2020)
This chapter explores whether the case law of the Court of Justice of the European Union (CJEU) produces any impact on the Turkish legal system and, if so, its possible underlying causes. Protection of intellectual, industrial, and commercial property rights, competition, trade defence instruments, government procurement, direct and indirect taxation have been regarded as the main areas of ‘approximation of legislation’. Accordingly, laws adopted mostly in the past three decades show that the influence of EU law is valid only in certain fields of law, such as intellectual property law, labour law, and competition law, and this is also where we find most CJEU citations. This influence forms part of the EU accession process, which requires Turkey to harmonize its laws with the acquis. According to the research, despite the existence of a long-standing accession process and legislation based on the acquis in certain fields of law, on the whole, the Turkish judiciary does not seem committed to follow EU law in general or CJEU jurisprudence in particular. © The Several Contributors 2020.
Keywords: Acquis Communautaire; Case Law; Court Of Justice Of The European Union; Eu Law; Judiciary; Turkey